2014
DOI: 10.1038/ncb2926
|View full text |Cite
|
Sign up to set email alerts
|

The role of differential VE-cadherin dynamics in cell rearrangement during angiogenesis

Abstract: Endothelial cells show surprising cell rearrangement behaviour during angiogenic sprouting; however, the underlying mechanisms and functional importance remain unclear. By combining computational modelling with experimentation, we identify that Notch/VEGFR-regulated differential dynamics of VE-cadherin junctions drive functional endothelial cell rearrangements during sprouting. We propose that continual flux in Notch signalling levels in individual cells results in differential VE-cadherin turnover and junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
432
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(446 citation statements)
references
References 58 publications
13
432
0
1
Order By: Relevance
“…First of all, we have assumed that tip cells maintain their fate for the duration of the entire vascular elongation or until anastomosis events. However, it is useful to underline that few recent in vivo and in vitro studies have shown that, at least in some situations, a dynamic and continuous phenotypic interchange between stalk and tip individuals may also occur [3,5,28]. The hypotheses underlying the role played by the two VEGF isoforms are of course a simplified setting of the "real" physiological picture, although they are commonly accepted and used in the computational literature.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, we have assumed that tip cells maintain their fate for the duration of the entire vascular elongation or until anastomosis events. However, it is useful to underline that few recent in vivo and in vitro studies have shown that, at least in some situations, a dynamic and continuous phenotypic interchange between stalk and tip individuals may also occur [3,5,28]. The hypotheses underlying the role played by the two VEGF isoforms are of course a simplified setting of the "real" physiological picture, although they are commonly accepted and used in the computational literature.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Recently, it has been shown that these TC and SC phenotypes are in fact transient states and the cells are constantly reshuffling positions. 9,11 Dynamic transitioning of TC and SC fates and positions is essential for effective patterning and expansion of the vascular network and is dependent on differential Dll4 expression and reorganization of the cell-cell junctions. 2,9,11 Under physiological conditions, the angiogenic response is tightly controlled suggesting the existence of negative regulators that limit or restrict tip cell formation.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying ways to isolate the cortical from transcriptional pathway of Notch may provide new opportunities to control these devastating complications. Furthermore, quantitative differences in expression of Notch and Dll4 in different vascular beds, described as a key mechanism for tip/stalk cell specification in angiogenesis 30 , may underlie differences in shear sensitivity and baseline permeability in organ-specific vascular beds. More broadly, the combination of a non-canonical pathway that regulates adhesive and cytoskeletal processes together with a transcriptional regulator of cell fate programs, channeled through a single receptor, provides a new framework for understanding coordinated developmental programs such as stem cell differentiation and tissue morphogenesis.…”
mentioning
confidence: 99%